Project-Based Learning in Teaching EFL Writing: An Analysis of the Effect on The 5 Dimensions of Writing - Wardani, Ni Komang Sri; Artini, Luh Putu; Ramendra, Dewa Putu (LPPM Undiksha, 2021)
Education has begun to see important constructivism in recent years to create effective teaching/learning strategies. There are several teaching models which are constructed based on constructivist theory. One of those models is Project-Based Learning. This study aims to analyze the effect of Project-Based Learning on students’ writing skill of grade IX students. This study implied embedded mixed method design, in which the quantitative data were considered as the main data. The data were collected through guided interview, observation, open-ended questionnaire, and writing test. Paired-sample t-test was used to analyze whether or not there is a significant difference in students’ writing skill before and after being taught using PBL, and Manova was used to analyze how project-based learning affected students’ writing skill in term of content, organization, structure, vocabulary, and mechanic. While the qualitative data were analyzed descriptively. The result showed that Project-Based Learning has significant effect on students’ English writing skill and it also affected the students’ writing skill in term of content, organization, structure, vocabulary, and mechanic (sig. =0.000 < α =0.05). Project-Based Learning also revealed potentially promotes students’ critical thinking, creativity, collaborative work, and enhances teacher’s satisfaction in teaching. In general, it can be concluded that Project-Based Learning significantly improves students’ writing skill of the grade IX students.